Transmission protocol selection for dual‐hop amplify‐and‐forward relaying networks. Issue 3 (1st September 2013) - Yingnan, Zhang
Abstract : This study solves the problem of transmission protocol selection for dual‐hop amplify‐and‐forward relaying networks. The two available protocols are parallel and non‐parallel, and the selection metric is the system data rate. First, for the non‐parallel protocol, the joint optimal power allocation (PA) scheme is derived using a single parameter optimisation approach. Secondly, for the parallel protocol, the optimal PA scheme is obtained through introducing a novel interval splitting approach, which considerably reduces the solution space from exponential to polynomial order. Finally, based on the proposed optimal PA schemes, the rate performance of the two protocols are compared, which reveals that their relationship is decided by the given average power constraint. The critical value of the average power constraint, above which the performance of the non‐parallel protocol outperforms that of the parallel protocol, is determined via numerical simulations. Therefore the critical value provides a selection criterion between the two protocols under data rate metric.